Pengaruh Investasi Hijau, Kinerja Lingkungan, Dan Profitabilitas Terhadap Carbon Emission Disclosure - Dwi Retnowati; Wulandari Cahyani Putri (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to examine the effect of Green Investment, environmental performance and profitability on Carbon emission disclosure in Basic Materials companies listed on the Indonesia Stock Exchange (BEI) during the 2018-2022 period. This study uses a quantitative approach and uses associative methods. The type of data used in this research is secondary data. The data analysis method used in this research is panel data regression using the Eviews version 10 application and Microsoft Excel. The population used in this study is Basic Materials Companies Listed on the Indonesia Stock Exchange for the 2018-2022 period. The data collection technique in this study was a purposive sampling technique with the results of 27 sample companies being processed in this study. The research results show that Green Investment, environmental performance and profitability simultaneously influence Carbon emission disclosure. Partially, Green Investment has an effect on Carbon emission disclosure, environmental performance and profitability have no effect on Carbon emission disclosure.